Underwater Accoustics Channel Modelling - Bansal, Sonu (My University, 2008)
The topic of this thesis is Underwater Acoustic (UWA) Communication Channel Modeling. Today, application of UWA communication is shifting from military towards commercial. Achieving high data rate transmission underwater is very challenging task because there is severe signal degradation takes place underwater because of multipath, spatial and temporal variability of the channel. The objective of this thesis is to introduce a novel UWA channel model which is suitable for simulation and can help in designing of UWA communication system. The dependency of noise, transmission range and transmission loss on frequency is discussed. Based on these characteristics of underwater channel achievable transmission range and acoustic power which can be transmitted for a particular transmission range is determined. A channel model based on channel geometry and environmental condition is presented. Amplitude and delay associated with each multipath is considered in channel model. Number of significant multipaths, for worst case, which have significant amplitude, is calculated for both directional and non-directional receiver. A measure of performance SMR (signal-to-multipath ratio) is introduced and based on that a condition for error free transmission is determined. SMR can be used to find transmitter or receiver depth for optimum transmission. In the last, A multipath Underwater Acoustic (UWA) communication channel model is simulated, using Simulink, based upon number of multipaths derived earlier for different parameters like wind speed, carrier frequency, reflection coefficient etc. of Underwater Acoustic (UWA) channel. BER is calculated for QPSK and QAM modulation schemes which are then compared with the BER, when same modulated signal is transmitted through AWGN channel and Rayleigh fading channel.
Keywords: Underwater; Channle